42 Straight line vs true distance to nearest aed – does it matter for cardiac arrest coverage?. (21st May 2017) - Karlsson, LIM; Sondergaard, KB; Hansen, CM; Wissenberg, M; Hansen, SM; Lippert, FK; Rajan, S; Kragholm, K; Møller, S; Gislason, GH; Torp-Pedersen, C; Folke, F
Abstract : Aim: International guidelines recommend automated external defibrillators (AEDs) to be deployed within 1_ min brisk walk distance to high-risk out-of-hospital cardiac arrest (OHCA) locations. Most studies translate this to a straight line distance of 100m while the true distance may be longer. We aimed to investigate how straight line versus true distances affected the AED coverage of nearby OHCA. Methods: We identified all OHCAs (2002–2014) and all public available AEDs in 2014, in Copenhagen, Denmark. Each arrest and AED was geocoded and straight line and true distance from arrest to the nearest AED was calculated. An OHCA was defined as covered by an AED if≤100m. Results: Of 4507 OHCAs, 22.3% occurred in public (n=1003) and 77.7% (n=3504) in residential locations. In 2014, there were 1134 public available AEDs. In total, the median distance in straight line was 148m (interquartile range (IQR):87–226), versus 224m (IQR:128–343) in true distance, with an AED coverage of 30.9% (n=1394), versus 18.5% (n=832), respectively. For public arrests, the median distance and AED coverage in straight line was 107m (IQR:53–185) and 48.1% (n=482), versus 167m (IQR:70–274) and 33.6% (n=337) in true distances. The corresponding numbers for residential OHCAs were 158m (IQR:98–239) and 26.0% (n=912) for straight line distance, versus 241m (IQR:146–354) and 14.1% (n=495) for true distance. Conclusion: Using true instead of straight line distance provides a more realistic estimation of AED coverage and could help improve public access defibrillation programs. Conflict of interest: None declared. Funding: Dr. L. I. M. Karlsson is supported by a fund from The Danish foundation TrygFonden, who has no influence on study design; in the collection, analysis, or interpretation of data.